"Заповіт" Шевченка в контексті жанру - Левчук, Тереза Петрівна; Levchuk, Tereza P. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Активним жанротворчим чинником заповіту є ідейно-змістовий мотив. Численні приклади таких віршів у світовій ліриці канонізували жанр вірша-заповіту. Існують апокрифічні, елегійні та сатиричні зразки цього жанру. В українській літературі заповіт як жанр утвердився у творчості Тараса Шевченка, поєднавши особисте й національне начала у високохудожній поетичній формі.

Ideological and semantic motif is an active factor in genre matrix of testament. A large number of poems canonized genre of verse-testament in world lyrics. There are apocryphal, elegiac and satirical examples of this genre. R. Herrick, John Donne, D. Huramishvyly, J. Laper, M. Lermontov, J. Slovatskyy, H. Botev, V. Nezval, F. Garcia Lorca, P. Pasolini, N. Gumilev, N. Zabolotskii and other authors wrote poems in this genre. Image of a subject expression of will, which expresses the value orientations of the author has determining value in the structural and semantic integrity of the poetic testament. This genre established in ukrainian literature with T. Shevchenko’s poems, that combines personal and national principle in highly poetic form. The idea of spiritual testament were continued in the work of many Ukrainian writers of the 19th and 20th centuries. In this nmber – I. Franko, Lesia Ukrainka, V. Symonenko etc.
Shevchenko’s "Testament" in the Context of the Ggenre
Keywords: жанр; основний мотив; вірш-заповіт; романтичне світосприйняття; традиція; genre; the main motive; poem-testament; romantic attitude; tradition